Interpreting the Motivation of Implementing Risk Management from Aristotle's Perspective - Aviani Widyastuti; Sri Iswati (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
This study aims to describe the implementation of Risk Management (RM) in business organizations represented by one of Indonesia's Fintech and Manufacturing sector companies from the perspective of Aristotle's Virtue theory. The two informants are used to get different perspectives on the regulations governing the implementation of RM. Through a semi-structured interview, we can illustrate that the two companies have implemented RM with various constraints and challenges, including each organization's characteristics and default risks. However, the implementation of RM is not only driven by the motivation of financial success but also ensures the sustainability of the company by considering all stakeholders' interests. This is in line with the principle of Virtue in Aristotle, which states that an organization's decision needs to consider Teleology, Habituation, noble pressure, Phronesis, social Virtue, and moral and intellectual superiority. Aristotle's principle of Virtue can be used as a basic framework for building an RM system in a business organization. Integrating the principle of Virtue into the RM system can create an organizational risk culture based on Virtue.